CTK Insights

02 Jul

An Engaging Algebraic Identity

A question has been asked on a linkedin group to prove the following engaging identity

Prove

(\frac{b-c}{a} + \frac{c-a}{b}+ \frac{a-b}{c})(\frac{a}{b-c}+\frac{b}{c-a}+\frac{c}{a-b})=9,

provided a+b+c=0.

One of the posts pointed to a solution at Stevens Society of Mathematicians. What follows is a slight simplification of that proof.

Denote the left factor L(a,b,c) and the right factor R(a,b,c). Observe that whenever two of the arguments in R are equal, the whole expression vanishes. For example,

\begin{align}L(a,a,c)&=\frac{a-c}{a}+\frac{c-a}{a}+\frac{a-a}{c} \\ &=\frac{a-c}{a}-\frac{a-c}{a}=0.\end{align}

Adding the fractions in L(a,b,c), L(a,b,c)=\frac{L'(a,b,c)}{abc}. What we just showed implies that the numerator L' is divisible by (a-b)(b-c)(c-a). Multiplying through confirms that L'(a,b,c)=-(a-b)(b-c)(c-a).

Now, let's turn to the right factor. Up to now we have not used the condition a+b+c=0. It's time we do. Introduce

\begin{cases}x = b - c \\ y = c - a \\ z = a - b.\end{cases}

Seen as a system of linear equations with a,b,c as unknown, it's degenerate because x+y+z=0. The situation improves if we replace any of the equations with a+b+c=0. Then, for example,

\begin{align}y-z &= (c-a)-(a-b) \\ &= (b+c)-2a \\ &=-3a. \end{align}

Similarly, -3b=z-x and -3c=x-y. This allows us to express the right factor R(a,b,c) in terms of x,y,z:

R(a,b,c)=-\frac{1}{3} (\frac {y-z} {x} + \frac {z-x} {y} + \frac {x-y} {z} ).

This is exactly the same form as L(a,b,c), implying that

R(a,b,c)=\frac{1}{3}\frac{(y-z)(z-x)(x-y)}{xyz}=-9\frac{abc}{(b-c)(c-a)(a-b)}.

Finally, L(a,b,c) \cdot R(a,b,c) = 9.

Leave a Reply


− 2 = zero

© 2014 CTK Insights | Entries (RSS) and Comments (RSS)

Powered by Wordpress, design by Web4 Sudoku, based on Pinkline by GPS Gazette